‘Measuring’ Adultery in Article 284 of the Criminal Code - Desjardins, Ajeng Kamaratih (Yayasan Jurnal Perempuan, 2018)
After the resolution about the petition of extending the meaning of adultery rampant discussed in the community, Article 284 KUHP is still an interesting article to be reviewed. Diversity in the Indonesian community causes a number of applied regulations must become as fair as possible to be a legal protection for all layers of society, including the regulations ruling the crimes of decency. Different understanding about violating decency in some community groups causes the article in Decency Crime section, especially in adultery case, often marginalizes some groups of community. There are indeed some group that might be potential to be victims of adultery cases if the meaning of adultery ever happens to be broadened. Further in its application, Article 284 KUHP makes the line between morality and crime becomes very thin. This research is done using the approach of feminist legal theory, by reviewing legal text to get an understanding on how sexuality and imagination about the woman victim is projected by law.